Left Ventricular Pseudoaneurysmectomy and Mitral Valve Replacement 30 Years after Blunt Polytrauma - Praet, Karel M. Van; Kofler, Markus; Kruse, Lilia; Solowjowa, Natalia; Hennig, Felix; Stamm, Christof; Unbehaun, Axel; Starck, Christoph; Jacobs, Stephan; Kempfert, Jörg; et al. (Archives of Clinical and Medical Case Reports, 2019)
Left ventricular (LV) pseudoaneurysms are the consequence of cardiac rupture, usually contained by adherent pericardium or fibrous scar tissue. They represent, from a functional point of view, the acquired blood-filled spaces that are external to the cardiac chambers but communicating with the ventricle. They can occur after transmural myocardial infarction or, albeit less frequently, post-traumatically. This cardiac disease has been a topic of discussion since the pioneering days of heart surgery. We present a case of a posttraumatic LV pseudoaneurysm, in which the causative blunt trauma happened 30 years prior to the onset of symptoms. Severe functional mitral regurgitation (FMR) resulted from leaflet tethering and partial rupture of the posteromedial papillary muscle complex.